Rotated Z^n-Lattices via Real Subfields of Q(ζ_2r) - Andrade, Antonio A.; Interlando, José C. (Trends in Computational and Applied Mathematics, 2019)
A method for constructing rotated Z^n-lattices, with n a power of 2, based on totally real subfields of the cyclotomic field Q(ζ_{2^r}), where r≥ 4 is an integer, is presented. Lattices exhibiting full diversity in some dimensions n not previously addressed are obtained.